2006
DOI: 10.1128/mcb.26.3.762-776.2006
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Mitochondrial Protein Turnover: Identification of Novel Substrate Proteins of the Matrix Protease Pim1

Abstract: ATP-dependent oligomeric proteases are major components of cellular protein quality control systems. To investigate the role of proteolytic processes in the maintenance of mitochondrial functions, we analyzed the dynamic behavior of the mitochondrial proteome of Saccharomyces cerevisiae by two-dimensional (2D) polyacrylamide gel electrophoresis. By a characterization of the influence of temperature on protein turnover in isolated mitochondria, we were able to define four groups of proteins showing a differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 53 publications
(76 reference statements)
3
92
0
Order By: Relevance
“…In this classical pathway, the antigenic peptide derives from cytosolic CLPP polypeptides before addressing to mitochondria. Another possibility is that CLPP is degraded by intramitochondrial proteolytic systems such as Pim1, other proteases of the AAA family (42,43), or the CLPP system itself. The resulting peptides are actively transported across the inner mitochondrial membrane into the intermembrane space, then cross the outer membrane by passive diffusion through porins or through the general import pore of the outer membrane (44).…”
Section: Discussionmentioning
confidence: 99%
“…In this classical pathway, the antigenic peptide derives from cytosolic CLPP polypeptides before addressing to mitochondria. Another possibility is that CLPP is degraded by intramitochondrial proteolytic systems such as Pim1, other proteases of the AAA family (42,43), or the CLPP system itself. The resulting peptides are actively transported across the inner mitochondrial membrane into the intermembrane space, then cross the outer membrane by passive diffusion through porins or through the general import pore of the outer membrane (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that during the absence of substrates or cosubstrates a catalytic center or a metal binding site of a protein may be damaged; similarly, a protein can undergo structural perturbation without other components that normally hold it in native conformation (7,17,18,(31)(32)(33)41). These proteins could display a nonfunctional, unprotected, or even "unemployed" state, and it can be hypothesized that ATP-dependent proteases recognize these idle and defective proteins and degrade them.…”
Section: Discussionmentioning
confidence: 99%
“…SOD2, peroxiredoxin3, mitochondrial thioredoxin, and mitochondrial thioredoxin reductase have been found to be the main components of the antioxidant system (20)(21)(22). Mitochondria are considered a principle source and target of reactive oxygen species (ROS) (23), and the collapse of the mitochondrial transmembrane potential can initiate the signaling cascades involved in apoptosis (24)(25)(26). It is well known that the cause of ADR cardiotoxicity is multifactorial, even though most ADR-induced cardiac effects can be attributed to ROS formation, which ultimately results in myocyte apoptosis (2).…”
Section: Cardiotoxicitymentioning
confidence: 99%